MAPLE VISUALIZATION TOOLS FOR A FRACTIONAL ORDER DISCRETE SYSTEM PERTURBED BY A SEQUENCE OF REAL RANDOM VARIABLES - Madalina Roxana Buneci (Fiabilitate şi Durabilitate)
The purpose of this paper is provide various Maple procedures to visualize the behavior of a general fractional order discrete systems perturbed by a sequence of real random variables.